1927
DOI: 10.1084/jem.45.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Paratyphoid Infection in Guinea Pigs

Abstract: Factors bearing on the maintenance of paratyphoid in an endemic state are discussed. There was no evidence of any increase nor any dearly demonstrable proof of a decline in virulence of the causative organism. This persisted within the breeding stock and it is suggested that the sows constituted the chief focus for dissemination of the organism to their young and from these to the population at large. Evidence is presented that the carriage of B. paratyphi in the feces was of relatively short duration. Fecal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1928
1928
1976
1976

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…seems to bear out the suggestion made in a previous paper that specific fecal excretion with adult guinea pigs is of relatively short duration (5).…”
Section: Discussionsupporting
confidence: 58%
“…seems to bear out the suggestion made in a previous paper that specific fecal excretion with adult guinea pigs is of relatively short duration (5).…”
Section: Discussionsupporting
confidence: 58%
“…The last-named author suggested that infection of guinea-pigs with salmonellae might occur by the respiratory route as well as by mouth. Smith & Nelson (1927) fed two adult and four recently weaned guinea-pigs through a pipette with doses of 800,000,000 Salm. typhi-murium; no disease followed.…”
mentioning
confidence: 99%